Energy Transition in Azerbaijan: Advantages of System Value Analysis and Strategic Role of the Global Climate Actors - Atiye Beyhan Akay; Sanem Özer; Senem Atvur (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Azerbaijan, a country with hydrocarbon resources, seeks to restructure its economy and energy system to become more resilient to climate change. The European Union's call for international climate action offers opportunities for a green energy transition in Azerbaijan. However, the economic, social, climatic, and environmental elements driving this transition are understudied. This article follows the example of the World Economic Forum’s System Value Analysis to study how complementary the impact of policies and solutions targeting sustainable development, the environment, climate action, and the green energy transition is in Azerbaijan. For this purpose, we analyze the energy market in Azerbaijan and the potential of renewable energy resources. The main aim is to reveal not only the economic advantages of the energy transition but also its political and strategic contribution to Azerbaijan. We argue that Azerbaijan's strategic engagement with the EU is crucial, as it serves as a means for Europe to bolster energy security and assist Azerbaijan in its political drive and strategy for transitioning to green energy. Additionally, it fulfills Azerbaijan's commitments to global climate initiatives.